Clowning Around with Conservation: Adaptation, Reparation and the New Substitution Problem. (1st April 2014) - Hale, Benjamin; Lee, Alexander; Hermans, Adam
Abstract : In this paper we introduce the 'New Substitution Problem' which, on its face, presents a problem for adaptation proposals that are justified by appeal to obligations of reparation. In contrast to the standard view, which is that obligations of reparation require that one restore lost value, we propose instead that obligations to aid and assist species and ecosystems in adaptation, in particular, follow from a failure to adequately justify - either by absence, neglect, omission or malice - actions that caused, or coalesced to cause, climatic change. Because this position suggests a different reason for reparation - namely, it does not rely on the notion that an obligation to repair is contingent upon a lost good - it permits moving forward with assisted colonisation and migration, but does so without falling subject to the complications of the New Substitution Problem.